2010
DOI: 10.1111/j.1468-1331.2010.03007.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of admission characteristics, hospital length of stay and costs for cerebral infarction in a medium‐sized city in China

Abstract: Stroke severity, OCSP classification, raised leukocytes on admission, some comorbidities, and medical insurance status may help to predict LOS for patients with cerebral infarction. Healthcare expenditures were heavy burdens to inhabitants. State medicine patients could shorten unnecessary LOS to improve the resources allocation and cost-efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 35 publications
4
38
3
Order By: Relevance
“…The findings of the multiple linear regression analysis were unlike much previous research [18, 19] in that people with the new cooperative medical scheme had a longer LOS than people with Urban Resident Basic Medical Insurance and with Urban Employee Basic Medical Insurance. Despite a relatively high coverage of medical insurance in China, the coverage provided by different types of social medical insurance in the country varies greatly.…”
Section: Discussioncontrasting
confidence: 99%
“…The findings of the multiple linear regression analysis were unlike much previous research [18, 19] in that people with the new cooperative medical scheme had a longer LOS than people with Urban Resident Basic Medical Insurance and with Urban Employee Basic Medical Insurance. Despite a relatively high coverage of medical insurance in China, the coverage provided by different types of social medical insurance in the country varies greatly.…”
Section: Discussioncontrasting
confidence: 99%
“…While it is difficult to directly compare this study with previous studies due to the use of different categories of charge (or cost) data,3,7,12,18,21 comparison was made possible by reorganizing the charges of similar items. In particular, three categories - pharmaceutical care, laboratory tests, and imaging studies - were comparable.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that the total cost of hospitalization due to stroke was significantly associated with the length of stay (LOS), stroke severity, clinical subtype, and certain sociodemographic factors,3,6-10 of which LOS was found to be the most decisive factor in determining the total cost of hospitalization of stroke patients 3,7,11. This has led to suggestions that shortening the LOS would be an effective and critical strategy for managing healthcare costs 12,13…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the cost was significantly higher for younger patients, which may indicate that physicians may offer more active treatment plans for younger patients. It has been identified that medical insurance type influences on stroke treatment costs [6,15]. Cost per stay associated with URBMI and NRCMI program was significantly higher than poverty relief and free medical service program with a difference of around 1,800 USD per stay, probably because both programs push hospitals to control cost with shorter LoS.…”
Section: Discussionmentioning
confidence: 99%